Symbolism in ritual: an example of Teochew opera performance among the Malaysian Chinese - Lin, Ziqiao; Ang, Mei Foong; Chieng, Julia (Elite Scientific Publications, 2024)
In the diverse cultural landscape of Malaysia, Teochew opera, a theatrical tradition with its origin in China, serves as a significant aspect of the ritual practices within the Chinese community that are constituted by perceptible symbols that accumulate distinctive attributes and specific meanings over time. Teochew opera in Malaysia conveys symbols through performance, fostering symbolic interactions and meaning-making. Nevertheless, the symbolic nuances of Teochew opera often remain enigmatic to other ethnic groups within Malaysia and tend to be obscured even among the Chinese community, where alternative forms of entertainment and cultural expressions hold sway. Consequently, this study aims to elucidate the characteristics of ritualised Teochew opera and chronicle the timing and objectives of these performances through participant observation in fieldwork. The ritualised performances of Teochew opera are deliberately timed, aligning predominantly with celebrations of gods, ghosts, and ancestors pertinent to the Malaysian Chinese community. Besides, the study examines the scripted performance of Carp Jumping Dragon Gate as an example, observed that Teochew opera predominantly employs visual symbols as the primary means of conveying symbolic meaning; their signifiers and signifieds are distinctly recognisable, allowing participants to decode the embedded messages from the pictorial cues. Auditory symbols, especially in some music, facilitate the elicitation of narratives and acquire significance through personalised interpretation and the integration of meaningful lyrics, titles and characteristic instrumentations. These performances symbolically articulate the community’s aspirational and pragmatic yearnings, such as seeking blessings and warding off malevolent forces. By examining the symbolism of Teochew opera, this study anticipates an expansion of cultural comprehension among varied ethnic groups in Malaysia.